Navigating the energy crisis: automakers’ coopetition strategies under dual credit policy - Yuan Kaifu; Wang Chuanji; Xiao Fang (Science and Technology for Energy Transition)
To tackle the energy and climate crises and achieve sustainable development, China has designated the development of new energy vehicles (NEVs) as a national strategy. This paper delves into the coopetition strategy of dual-model automakers under the dual credit policy (DCP) using a subsidy-R&D-production three-stage game model, considering government subsidies and consumer preferences. The model explores various strategies, including full competition and different R&D cooperation scenarios for fuel vehicles (FVs) and NEVs. Key findings include: (1) R&D subsidies boost NEVs R&D investments but may not always optimize social welfare. (2) When NEVs technology spillovers are low, firms should fully cooperate; otherwise, the FVs R&D cooperation is optimal, especially with high FVs spillovers. (3) Investments and outputs in both vehicle types positively correlate with technology spillovers, and consumer preferences. Conversely, FVs equilibrium decreases with NEVs credit proportion and fuel consumption disparities. (4) The credit price positively influences R&D investments and outputs of NEVs, but its effects on FVs’ R&D investments, outputs, corporate profits, and social welfare vary based on market dynamics. Recommendations include optimizing subsidy policies, supporting low-carbon FVs, enhancing infrastructure, and strengthening DCP regulations to stabilize credit price expectations.